Prevalence, Awareness, Treatment, and Control of Hypertension and Diabetes: Results From Two State-Wide STEPS Survey in Punjab and Haryana, India - J. S. Thakur; Ria Nangia (Frontiers Media S.A., 2022)
BackgroundIndia which is home to more than one sixth of the world's population, accounts for more than two thirds of total deaths due to non-communicable diseases (NCD). Out of this, hypertension and diabetes are the most common NCDs. Awareness, treatment, and control of hypertension and diabetes remains a major challenge despite various national programs being run to curb the rising burden NCDs. In order to fill the knowledge gap, awareness, treatment, and control of diabetes and hypertension were studied by using data from the STEPS survey among the adult population in two major northern Indian states of Punjab and Haryana.MethodsTwo state-wide NCD risk factors surveys were conducted using WHO STEPS methodology among 5,127 individuals in Punjab and 5,078 individuals in Haryana aged 18-69 years in the year 2014-15 and 2016-18. Standardized questionnaire was used to determine the behavioral risk factors in step one followed by anthropometric measurements for physical risk factors in step two and in the third step serum and urine samples were collected for biochemical risk factors.ResultsThe prevalence of hypertension in Punjab was 40.1% while that in Haryana was 26.2%. In Punjab, only 48.3% of the hypertensive were aware of their condition, 30.9% were on treatment while only 18.3% of the cases were controlled. While in Haryana 33.4% of the respondents were aware of their condition, 26.3% are on treatment while only 12% of the cases were controlled. Similarly, the prevalence of diabetes was 14.3 and 15.1% in Punjab and Haryana, respectively. In Punjab 34.2% of diabetics were aware of their condition, 28.2% were on treatment while only 14.2% of the cases were controlled. The awareness and control rates in Haryana were similar to that in Punjab. 29.5% of the respondents were aware of their condition, 22.4% were on treatment while only 13.8% of the cases of diabetes were controlled. Family history of diabetes and hypertension was found to be associated with higher odds of being aware, on treatment and controlled blood glucose and blood pressure levels in both Punjab and Haryana.DiscussionHypertension and diabetes are a major public health problem in Punjab and Haryana and awareness, treatment and control rates are low which require specific interventions with a focus on access to treatment, regular follow up for better control. There is an urgent need to effectively implement the existing national NCD programmes in these states in India.